100 algorithms challenge (Manning Publications, 2022)
Technical interviews are the filter between good and great developers. At least that is how the industry sees them. In this course, we will improve your problem solving ability as well as your speed with 100 algorithm problems and solutions. These questions are some of the most commonly asked in interviews--including interviews with Google, Facebook, Uber, Amazon, and other top tech companies. By the end of the course you will: Have a handle on higher order functions in JavaScript Understand the basics of TypeScript Have a 100-algorithm portfolio item Be ready to ace the JavaScript technical interview.